The effects of eye movements and alternative dual tasks on the vividness and emotionality of negative autobiographical memories: A meta-analysis of laboratory studies. Issue 1 (16th March 2020) - Houben, Sanne T. L.; Otgaar, Henry; Roelofs, Jeffrey; Merckelbach, Harald; Muris, Peter
Performing eye movements during memory retrieval is considered to be important for the therapeutic effect of eye movement desensitization and reprocessing (EMDR). We conducted a meta-analysis of laboratory studies that compared the effects of eye movements and/or alternative dual tasks (e.g., counting) on the vividness and emotionality of negative autobiographical memories with recall only (control) conditions. The databases PsycINFO and Web of Science were queried. Fifteen studies that involved 942 participants were included. Eye movements and alternative dual tasks produced similar vividness and emotionality decreases, with the impact on vividness being strong than that on emotionality. However, eye movements yielded a stronger overall vividness reduction than alternative dual tasks, although the associated effect size was small (Cohen's d = .29). Because eye movements and alternative dual tasks produced comparable effects, one might conclude that both tasks are therapeutic equivalents. However, it should be acknowledged that only a limited number of laboratory studies were included in our meta-analysis, and the degree to which both procedures tax working memory was not independently established. Although our conclusion cannot be generalized to clinical practice, it does raise questions about the mode of action of EMDR.